2011
DOI: 10.4028/www.scientific.net/amr.410.309
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Properties of Epoxy Composites Filled with Glass Powder: Preliminary Results

Abstract: Epoxy resin was filled with glass powder with a view to increasing strength of the composite for structural applications by a research Centre on composites, University of Southern Queensland (USQ). In order to reduce costs, the Centre wishes to fill as much glass powder as possible subject to maintaining sufficient strength of the composites in structural applications. This project varies the percentage by weight of the glass powder in the composites which are then subjected to flexural tests. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The trend of the values of the flexural modulus was the same with that of this study and that of Ray et al. The minimum value of flexural strength occurred at 15 % by weight of particulate loading; it then rose back to a maximum at 30 w/t % of filler before dropping down with higher particulate loading [8]. Figure 4 is the SEM image of 10% by weight of Sphericel 60P18 filled vinyl ester composite and the amount of porosity in the specimen was quite low due to the abundance of vinyl ester resin, which in turn gave it a high flexural strength.References…”
Section: Resultssupporting
confidence: 73%
“…The trend of the values of the flexural modulus was the same with that of this study and that of Ray et al. The minimum value of flexural strength occurred at 15 % by weight of particulate loading; it then rose back to a maximum at 30 w/t % of filler before dropping down with higher particulate loading [8]. Figure 4 is the SEM image of 10% by weight of Sphericel 60P18 filled vinyl ester composite and the amount of porosity in the specimen was quite low due to the abundance of vinyl ester resin, which in turn gave it a high flexural strength.References…”
Section: Resultssupporting
confidence: 73%
“…They reported that maximum fracture load of specimens increased with decreasing fiber lengths (p < 0.001) and fiber-containing group showed significantly higher fracture load than fiberless groups. Ku and Trade (2010) and Ku and Wong (2012) studied on bending properties of glass powder reinforced composite and they investigated that optimum powder concentration should be determined for different matrix elements for having higher flexural strength and modulus due to possibility of imperfection in interfacial bounding between matrix and reinforcing agent. Flexural fracture in WGFP reinforced composites is related with form of reinforcement material.…”
Section: Figure 7 Flexural Stress-strain Curves Of Samplesmentioning
confidence: 99%
“…Ku and Wong (2011) measured tensile strength behaviours of glass powder reinforced epoxy composites were measured and they claimed that glass powder was not a suitable filler and fractured surfaces were obtained. Ku and Wong (2012) tested mechanical properties of glass powder/vinyl ester composites and test results showed that strength of composites was less than neat matrix materials. Sonsakul and Boongsood (2017) produced glass fiber and glass scraps powder reinforced polyester composites and mechanical properties of composites such as impact resistance, tensile strength and flexural strength; reduced with powder reinforcement as oppose to fiber strengthening.…”
Section: Introductionmentioning
confidence: 99%